Inhibitory Effects of Tualang Honey on Experimental Breast Cancer in Rats: A Preliminary Study - Abd Kadir, Erazuliana; Sulaiman, Siti Amrah; Yahya, Nurul Khaiza; Othman, Nor Hayati (Asian Pacific Organization for Cancer Prevetion, 2013)
The study was conducted to determine the effect of Malaysian jungle Tualang Honey (TH) on development of breast cancer induced by the carcinogen 7,12-dimethylbenz(α)anthracene (DMBA) in rats. Forty nulliparous female Sprague-Dawley rats were given 80 mg/kg DMBA then randomly divided into four groups: Group 1 served as a Control while Groups 2, 3 and 4 received 0.2, 1.0 or 2.0 g/kg bodyweight/day of TH, respectively, for 150 days. Results showed that breast cancers in the TH-treated groups had slower size increment and smaller mean tumor size (≤2cm3 ) compared to Controls (≤8cm3 ). The number of cancers developing in TH-treated groups was also significantly fewer (P<0.05). Histological grading showed majority of TH–treated group cancers to be of grade 1 and 2 compared to grade 3 in controls. There was an increasing trend of apoptotic index (AI) seen in TH-treated groups with increasing dosage of Tualang Honey, however, the mean AI values of all TH-treated groups were not significantly different from the Control value (p>0.05). In conclusion, Tualang Honey exerted positive modulation effects on DMBA-induced breast cancers in rats in this preliminary study